Novel baculovirus-derived p67 subunit vaccines efficacious against East Coast fever in cattle - Kaba, S.A.; Musoke, A.J.; Schaap, D.; Schetters, T.; Rowlands, G.J.; Vermeulen, A.N.; Nene, Vishvanath M.; Vlak, J.M.; Oers, M.M. van (Elsevier, 2005)
Two novel baculovirus-derived recombinant Theileria parva p67 constructs were tested for their vaccine potential against East Coast fever. Boran calves were immunized with a his-GFP-p67 fusion protein (GFP:p67DeltaSS) or with GP64:p67C, a protein fusion between a C-terminal domain of p67 and the baculovirus envelope protein GP64. Both GFP:p67DeltaSS and GP64:p67C induced antibodies with high ELISA titers that neutralized T. parva sporozoites with high efficiency. Upon challenge, a correlation was observed between the in vitro neutralizing capacity and the reduction in severe ECF for individual animals. A protection level upto 85% was obtained. This level of protection was achieved with only two inoculations of 100mug per dose, which is a major improvement over previous recombinant p67 products.